„Перед зарей вас родила земля, погибнете вы раньше звезд вечерних”. Роман-памфлет Юрия Домбровского Обезьяна приходит за своим черепом - Knurowska, Monika (Studia Rossica Posnaniensia, 2021)
This article presents the thesis that the novel The ape is coming to pick up its skull (1943) by Yuri Dombrovsky bears the genre features of a pamphlet and the structure of the novel, which is subordinated to a didactic purpose – the work contains a warning against the dehumanization and degradation of culture. The novel aims to ridicule the fascists and their ideology. The narrator’s attitude towards all the fascist protagonists is dominated by irony and sarcasm. The character construction of the fascists is ruled by schematism. The narrator emphasizes the animal element in them. They are compared to an ape who is a caricature hybrid of a human and a monkey. The “monkey” traits and behaviours are highlighted in their portraits. In the novel, the dialogues and disputes of the main opponents serve to expose the cynical demagogy of fascism and its inability to create any universal values.